Odpowiedzi

2009-12-01T20:44:35+01:00
A) y+2-(3-x)=0
x-2=5-(2-y)

y+2-3+x=0
x-2=5-2+y

y+x=1
-y+x=3 +
----------------
2x=4
x=2

y+2=1
y=-1

b) 3(x-y)+4x=8
3(x-5y)=5-9y(tu zrobiles blad pewnie chodzilo o 3(x-5y)=5-9y a nie o 3(x-5y)=5=9y)

3x-3y+4x=8
3x-15y=5-9y

7x-3y=8/*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5 +
---------------------
-11x=-11
x=1

3*1-6y=5
-6y=2
y=-1/3

c) 3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=20
-5x-2y=4/*2

6x+4y=20
-10x-4y=8 +
-----------------
-4x=28
x=-7

6*(-7)+4y=20
-42+4y=20
4y=62
y=15.5

d) 2(x+y)-3(x-2y=-7x-2
5(x+1)-2(3-y)=-4(x+y)

2x+2y-3x+6y=-7x-2
5x+5-6+2y=-4x-4y

6x+8y=-2
9x+6y=1/*(-⅔)

6x+8y=-2
-6x-4y=-⅔ +
--------------------
4y=-2⅔
4y=-8/3
y=-8/3*1/4
y=-⅔

6x=10/3
x=5/9

e) 4(x+2) -3(y-1)=x+y-3
powinienes tu dokonczyc cale 2 rownanie przykro mi nie rozwiaze go;/
1 5 1